In The Pursuit of The Perfect Thyroid Care - Kumar Sahoo, Manas; Barron, Nahim (Journal of Thyroid Cancer, 2018)
A clinical perspective on optimizing thyroid care spans diagnostics, surgical indications, and long‑term follow‑up, aiming to align practice with patient goals and evidence.
Keywords: Thyroid; PET/CT; Thyroidectomy; SPECT/CT; 131I